Improving maternal health quality: reviewing the context and consequences - Chauhan, Anshul; Narayanan, Prakash; D'souza, Jyoshma (Indian Journal of Community Health, 2017)
Background: Approximately 99% of pregnancy-related deaths in developing countries are due to preventable causes related to pregnancy and childbirth which signifies that around 800 women die every day due to such causes. Major causes that lead to maternal deaths are post-partum hemorrhage, infections, high blood pressure and unsafe abortion. There are several facilities being provided for pregnant mothers yet the quality of care needs to be analyzed. Objectives: To understand the quality perspective of maternal health services and to review available evidence for strengthening maternal health services. Material & Methods: Research studies published between 2006 and 2016 were selected by specific inclusion criteria. Pub Med and Google Scholar were used to search studies on the topic, and few articles were identified through references and citations. Results: The result of the review highlighted the evidence of pitfalls, gaps in quality care, and need for interventions and approaches to improve the quality of maternal health care. Conclusion: Quality care encompasses various elements which stride towards improving the health of women and the interventions are to be scaled up to improve the quality of care. Generation of public health evidence and uniformity in quality assessments can help interventions to achieve desirable standards.